Bebop improvisation in guitar case study: stompin' at the savoy by Kenny Burrell / Mohd Noor Lattiff Norsham - Norsham, Mohd Noor Lattiff (2010)
The purpose of this research study is to extend the information on the characteristic and technique of Bebop Improvisation in Guitar. In order to get the exact interpretation and language of bebop style, characteristic and technique of guitar playing must be applied. For the purpose of this fundamental research topic, I have focused towards improvisation analysis based on the tunes; Stompin' at the Savoy by Kenny Burrell which was composed over advanced I-IV-II-V progression. Kenny Burrell one of the most influential bebop guitarist in his era and until now, he will be the guidance and reference to nowadays modem player especially youngsters. His idea towards bebop music was tremendously awesome with approaching the correct element of bebop characteristic and technique in his improvisation such as melodic approach in rhythmic way for example; space, syncopation and triplet. He also mastered the technique in guitar playing for instance picking technique and left hand technique of guitar such as hammer on and pull off technique.